Perbedaan Persepsi Gender Pada Mantan Staf Profesional Kantor Akuntan Publik - elma muncar aditya (Jurnal Ilmiah Aset, 2009)
The purpose of this research is to analyze the differences between the perception of male accounting firm alumni and female accounting firm alumni to their experience, accounting firm programs, and the possibility to hire their ex accounting firm. The data were collected through questionaire and the research was tested to 90 accounting firm alumni which is 63 male accounting firm alumni and 27 female accounting firm alumni. The hipothesis is tested using independent sample t-test. The results of this research are there is no significant perception differences between male and female accounting firm alumni to their experience (H1), there is no significant perception differences between male and female accounting firm alumni to the accounting firm programs (H2), and there is significant perception differences between male and female accounting firm alumni to the possibility to hire their ex accounting firm (H3).